Differentially regulated ADAMTS1, 8, 9, and 18 in pancreas adenocarcinoma - Murat Özgür Kılıç; Büşra Aynekin; Mikdat Bozer; Adem Kara; Hacer Haltaş; Duygu İçen; Kadir Demircan (Gastroenterology Review)
Introduction : Despite recent diagnostic and therapeutic improvements, pancreas cancer remains one of the highly lethal cancers. The extracellular matrix (ECM) is a physiological barrier that limits the spread of cancer cells into surrounding tissues and distant organs. Disintegrin and metalloprotease with thrombospondin motifs (ADAMTS) is a family of 19 proteases, which is involved in various biological processes such as ECM remodelling and anti-angiogenesis. Aim : To investigate the expression of ADAMTS1, 8, 9, and 18 proteinases in pancreas adenocarcinoma and its nodal metastasis. Material and methods : The immunostaining status of ADAMTS1, 8, 9, and 18 were investigated in formalin-fixed paraffin-embedded samples of 25 patients who underwent pancreaticoduodenectomy for an adenocarcinoma located at the head of the pancreas. Results : In semi-quantitive grading pathologically, ADAMTS1, 8, 9, and 18 were found to be highly stained in all cancerous pancreas samples compared with normal pancreas. In addition, the immune positivity of ADAMTS1, 9, and 18 was found to be higher in metastatic lymph nodes than in non-metastatic lymph tissue. Tumour size was correlated with ADAMTS9 and 18 expressions in cancerous pancreas. Conclusions : According to the data obtained from the study, we suggest that these four ADAMTSs may have significant roles in the tumorigenesis and nodal spread of pancreas adenocarcinoma.